Comparison of microbiota, antimicrobial resistance genes and mobile genetic elements in flies and the feces of sympatric animals. Issue 4 (27th February 2020) - Poudel, Anil; Kang, Yuan; Mandal, Rabindra K; Kalalah, Anwar; Butaye, Patrick; Hathcock, Terri; Kelly, Patrick; Walz, Paul; Macklin, Kenneth; Cattley, Russell; Price, Stuart; Adekanmbi, Folasade; et al.
ABSTRACT: Flies are well-known vectors of bacterial pathogens, but there are little data on their role in spreading microbial community and antimicrobial resistance. In this study, we compared the bacterial community, antimicrobial resistance genes (ARGs) and mobile genetic elements (MGEs) in flies with those in the feces of sympatric animals. A 16S rRNA -based microbial analysis identified 23 bacterial phyla in fecal samples and 25 phyla in flies; all the phyla identified in the fecal samples were also found in the flies. Bray–Curtis dissimilarity analysis showed that the microbiota of the flies were more similar to the microbiota of the feces of their sympatric animals than those of the feces from the three other animal species studied. The qPCR array amplified 276 ARGs/MGEs in fecal samples, and 216 ARGs/MGEs in the flies, while 198 of these genes were identified in both flies and feces. Long-term studies with larger sample numbers from more geospatially distinct populations and infection trials are indicated to further evaluate the possibility of flies as sentinels for antimicrobial resistance. Abstract : Comparison of the bacterial community and antimicrobial resistance genes in flies and feces in this study warrants further studies to evaluate the possibility of flies as sentinels for antimicrobial resistance transmission.